ECONOMIC SECURITY OF SMALL AGRICULTURAL ENTERPRISES - Boiko, M.V. (The actual problems of regional economy development, 2019)
The article “Economic Security of Small Agricultural Enterprises” aims at exploring the theoretical foundations of economic security for small agricultural enterprises. The basic approaches to definition of the category "economic security of the enterprise" are investigated. The theoretical bases of the definition of "economic security" are considered. The integration of Ukraine into the global economic space implies the modernization of the modern financial and economic system, which envisages the transition of market entities to a new level of relations and the leveling of traditional geographical boundaries. At the same time, the conditions of functioning of enterprises in a market environment become more stringent due to the expansion of the range of probable threats and dangers, which increase the risk level of conducting business activities, increasing uncertainty, and increasing competition. It is economic security that can provide the enterprise with effective functioning, economic stability, development and improvement of its competitiveness level. The main purpose of this work is to research and analyze the major achievements of economic science in the economic security of a small business and to present the author's vision of the essence of this concept. The set of research methods is the methodology of analysis and organization of major publications, legislation and laws, namely methods of generalization, comparison, chronologization, analysis and generalization. The author's vision of interpreting the concept of "economic security of enterprises" is a scientific novelty. The practical value of the study is to analyze the main publications on the definition of the essence of the concept of “economic security of the enterprise”, because today there is no single approach that would clearly interpret this concept.